A secure and efficient computation based multifactor authentication scheme for Intelligent IoT-enabled WSNs. (January 2023) - Kumar, Ravi; Singh, Samayveer; Singh, Pradeep Kumar
Abstract: In recent years, network-enabled physical devices have emerged as a solution to many problems, such as those involved in transmitting data from the physical world, communicating, and safeguarding information. The process of data transmission is vulnerable to a range of threats and must be secured because an open communication channel is considered for data transmission. One way to eliminate this security risk is by using a reliable and secure mutual authentication method. To accomplish this, a secure and reliable computation-based multifactor authentication approach is proposed for Intelligent IoT-enabled WSNs. To reduce the computational and communication overhead, a physically unclonable function-based secure authentication approach is proposed for sensor node's mutual authentication. In addition, to maintain the confidentiality of session key, a secure session is established among user, basestation, and nodes by using an adaptive session key update procedure. Moreover, formal and informal security analyses are performed for different aspects of security attacks.